(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This scientific work focuses on improving a comprehensive approach to the management of patients with coexisting benign tumors of the uterus and its appendages (such as myoma, cysts, fibroma, etc.) and genital prolapse. The study analyzes the clinical manifestations, diagnostic methods, and both surgical and conservative treatment strategies for such conditions. Special attention is given to developing individualized approaches aimed at improving patients’ quality of life, preventing complications, and reducing the risk of recurrence.